Phenolic Compounds as Nutraceuticals or Functional Food Ingredients - Caleja, Cristina; Ribeiro, Andreia; Filomena Barreiro, Maria; C.F.R. Ferreira, Isabel (Current Pharmaceutical Design, 2017)
Background: Nowadays, the functional foods represent one the most promising, interesting and innovative areas in the food industry. Various components are being added to foods in order to render them functional. Methods: One example of these components are plant naturally occurring phenolic compounds, which are associated with a high antioxidant capacity and thus with benefits in relation to human health. Results: However, despite the huge number of scientific studies and patents on this topic and their natural presence in foods, namely in the ones from plant origin, there are still few marketable products enriched with these compounds. The commercialization of this type of functional products needs to go through various regulations, proving that they are safe and present the ascribed health benefits, conquering the target audience. In this review the growing interest of industry and consumers’ appetence for functional foods and nutraceuticals is highlighted, focusing especially on phenolic compounds. Conclusion: Although several published works show the multitude of bioactive properties of these compounds, ensuring their use as bioactive ingredients in food, they present inherent stability issues needing to be solved. However, considerable research is presently ongoing to overcome this problem, making viable the development of new products to be launched in the market.
Keywords: consumers